FINDING SOLUTIONS TO PROBLEMS IN PUBLIC FINANCES AND IMPROVING SOME IMPORTANT PARTS - Jo’rayev Og’abek (Journals Park Publishing, 2023)
The formation of new approaches to the budgetary and financial policy of the state requires a change in the tools for monitoring the use of public funds. In connection with this, the issues of development and implementation in the practice of performance audit are raised, therefore, the article discusses the current problems of using this tool and determines the directions for their solution. The study of foreign experience in the operation of performance audit has made it possible to conduct a comparative analysis of audit objects, regulatory authorities and the features of its implementation in the USA, Canada and some other countries. Performance audit differs from financial audit and revision, it should be aimed at assessing the rational use of resources and the cost-effectiveness of the costs incurred, which gives rise to certain problems. This article raises the three most important problems of the practical implementation of performance audit in Russia and outlines ways to solve them.
Keywords: performance audit, revision, control, public funds, public finances.